PENGARUH FINANCIAL STABILITY, GOOD CORPORATE GOVERNANCE DAN INTERNAL CONTROL TERHADAP FRAUDULENT FINANCIAL FRAUD - Angelin, Debora; Kristanto, Septian Bayu (Jurnal Penelitian Akuntansi (JPA), 2025)
This research aims to examine the influence of financial stability, good corporate governance, and internal control on fraudulent financial fraud. This research is quantitative research. The data used is secondary data from company annual reports, obtained from each company's website. The population in this research is state-owned companies (BUMN) that are still operating in Indonesia. The sampling method in this research uses a purposive sampling method which produces a sample of 20 state-owned companies using annual reports and having complete data as required by the variables used for the 2021-2023 period. The method used to analyse the data is panel logistic regression analysis. The research results show that the Nagelkerke R Square value is 0.191, which means that financial stability, good corporate governance and internal control can explain 19.1% of fraudulent financial fraud and the rest is influenced by other variables outside this research. The test results show that: (1) financial stability has no effect on fraudulent financial fraud, (2) good corporate governance has no effect on fraudulent financial fraud, and (3) internal control reduces indications of fraudulent financial fraud.